Soil Mesofauna Community Changes in Response to the Environmental Gradients of Urbanization in Guangzhou City - Yu, Shiqin; Qiu, Junliang; Chen, Xiaohua; Luo, Xiaofeng; Yang, Xiankun; Wang, Faming; Xu, Guoliang (Frontiers in Ecology and Evolution, 2021)
Recently, there is an increasing interesting on how urbanization affects soil fauna community. However, previous studies primarily focused on some limited landuse types or line transect of urban-rural gradients. On family and higher taxonomic levels, we investigated the changes of soil mesofauna community with urbanization intensity along different disturbance features in 47 sites evenly located in Guangzhou downtown and the adjacent region. The 47 studied sites were classified into four ecosystem types with increasing urbanization intensity including rural forest, urban forest, urban woodland and urban park, mainly according to the location (rural/urban), vegetation cover, and management intensity. Firstly,the results showed that soil mesofauna abundance and diversity decreased with increasing soil pH, total nitrogen content (TN) and heavy metal comprehensive index (CPI). Soil Pb depressed soil mesofauna species richness and regulated soil mesofauna community structure.Secondly, we found impervious surface (IS) proportion did not predicate changes in soil mesofauna abundance, diversity or community structure. However, we found IS proportion were positively correlated with soil pH, soil TN and CPI. In contrast, site area was positively correlated with soil mesofauna abundance after excluding the sites belonged to rural forest and urban park. Site area was negatively correlated with soil pH and CPI. Thirdly, our results showed significant differences in soil property, landscape trait and soil mesofauna community among the four ecosystem types. Interestingly, urban forest, the one with light urbanization disturbance, had the highest soil mesofauna abundance. Our results also showed that urban woodland and urban park had distinct mesofauna community structures compared to those in rural forest and urban forest. In conclusion, the present study revealed that (1) soil property changes due to urbanization, such as increased pH and accumulated heavy metal in urban soil, depressed soil mesofauna abundance and diversity, changed community structure, and they mediated the effect of landscape change on soil mesofauna community; (2) however, soil and landscape changes could not explain the increase of abundance in urban forest, which supported the intermediate disturbance hypothesis.